EFFECIENCY OF VERMIK 1 % SOLUTION IN MIXED INTESTINAL NEMATOSIS OF PIGS - Антіпов, А. А.; Пономар, С. І.; Гончаренко, В. П.; Міськова, Ю. О.; Коваль, А. Ю. (Scientific Progress & Innovations, 2013)
The article presents data about spreading of swine mixed nematodosis on the farm, age dynamics and efficiency of Vermik 1 % solution. Research found that in nematosis of swine gastrointestinal channel of different age and production groups of swine, the pathogens of askarosis (EІ = 50,56 %), trihurosis (EІ = 10,56 %) and oesofagostomosis (EІ = 18,33 %) appear most often. The efficiency of antihelmintics of macro cyclical series Vermik 1 % injection at askarosis, trihurosis and oesofagostomosis (EE and ІE = 100,0 %) was defined.